Attentional mechanisms in sports via brain-electrical event-related potentials - Hack, J.; Memmert, D.; Rupp, A. (Research Quarterly for Exercise and Sport, 2009)
In this study, we examined attention processes in complex, sport-specific decision-making tasks without interdependencies from anticipation. Psychophysiological and performance data recorded from advanced and intermediate level basketball referees were compared. Event-related potentials obtained while judging game situations in foul recognition and a control task provided insight into focus of attention, selective attention, and processing strategy (top-down vs. bottom-up). Results showed task-specific effects for advanced referees in components influenced by attentional focus and selective attention. Experts also seemed to profit from superior top-down strategy and were able to evaluate the stimuli more rapidly. These findings are discussed in connection with current models in neurosciences and theories of referee research.